Review Sistem Drainase Parak Jambu Dadok Tunggul Hitam Padang Menggunakan Model EPA-SWMM - Mera, Mas; Februarman, Februarman; Aryadwitama Priadi, Fandi (Jurnal Bangunan, Konstruksi & Desain, 2024)
Flood disasters have been a never-ending problem for humans all over the world from the past to the present. This disaster can be caused by natural events or as a result of human activities and even by both simultaneously. One of the areas that often experiences flooding is the Parak Jambu Area, Dadok Tunggul Hitam Village in Padang City. This research objective is to overcome flooding that occurs in the area by means of numerical simulation using the EPA SWMM v.5.2 model. The existing conditions consist of 6 subcatchments in the Parak Jambu Area plus 28 supporting subcatchments located outside the area. All of them consist of 281 conduits (canals). The results of the simulation of existing conditions show that 32 canals are flooded and 6 canals do not carry any water at all. In dealing with the flooding that occurred, two approaches are taken, namely modifying the dimensions of the existing channels and adding new channels to the edge of the existing catchment. The simulation results of modified conditions show that there are no more canals that experience flooding in the Parak Jambu Area, and canals that previously did not carry water, now carry water.